New technologies in the ESP class for mechanical engineers - Gonzalez-Vera, Pilar (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
A substantial reform of Spanish universities and consequent adaptation of the teaching methods has been brought about by the European Higher Education Area. The central role of students, the importance of competences and skills as well as the erruption of technology in education finds a useful ally in Project Based Learning (PBL). This paper concentrates on the teaching of English for Specific Purposes (ESP) and aims to show the potential of digital devices, new technologies and audiovisual texts and translation to provide the practical instruction on technical English by creative and motivational activities that engage students in practical learning. The study focuses on mechanical engineering students and presents the activities that revolve around the main task: to design and sell a hybrid car.